International perspectives on comparative analysis - Guimarães, Paula (2022)
This thematic issue of Sisyphus aims at contributing to understanding diversity, fragmentation and complexity of comparison in adult education research, focussing on policy and practices developed in different parts of the world. The articles to be include in this issue are the outcome of the vivid discussion held in the INTALL Adult Education Academy 2021, promoted by the University of Würzburg, when the COVID-19 pandemic had a significant impact on every ones’ lives, in special in those attending this educational initiative. Joined by more than 60 students and 20 teaching staff from higher education institutions of 5 continents, the INTALL Adult Education Academy is a significant event to reflect critically about adult education comparison when a health situation constrained and still constrains mobility and face-to-face teaching.